The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1590/2175-7860202172028
|View full text |Cite
|
Sign up to set email alerts
|

Germination inhibitory activity of aqueous extracts of native grasses from South America

Abstract: Soluble allelochemicals have generated great interest since they can be used for the biological control of pests, especially of weeds. However, few studies have evaluated the effectiveness of soluble compounds of exudates on germination in relation to exposure time. Here we evaluate the inhibitory effect of aqueous root, stem and leaf extracts of five South American species of Bothriochloa on the percentage of seed germination of four target species (lettuce, lovegrass, maize and wintergreen paspalum) over thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Another functional trait identified was the ability of natives to self-protect, which can be both offensive and defensive. Offensive strategies include the usage of allelopathy to reduce germination rates in seeds of other species (Scrivanti and Anton, 2021). The South American native species of Bothriochloa spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another functional trait identified was the ability of natives to self-protect, which can be both offensive and defensive. Offensive strategies include the usage of allelopathy to reduce germination rates in seeds of other species (Scrivanti and Anton, 2021). The South American native species of Bothriochloa spp.…”
Section: Discussionmentioning
confidence: 99%
“…The South American native species of Bothriochloa spp. produced allelopathic chemicals that had a strong inhibitory effect on weed seed germination (Scrivanti and Anton, 2021). Conversely, a defensive approach is the ability of native species to resist allelopathy from weeds (Shang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Location Coordinates Aqueous extracts. In order to obtain the aqueous extracts, we used a method adapted from the one described by Scrivanti (Scrivanti 2010, Scrivanti et al 2011, Scrivanti & Anton 2019, 2021. Five grams of fresh leaf blades from each Imperata plant were crushed with a blender.…”
Section: Imperata Species Collection Number (Cord)mentioning
confidence: 99%
“…The allelopathic effect depends on the donor and recipient species, their growth stage, and the toxicity level of the released allelochemicals [1]. The study on grass species has demonstrated the existence of phenolic compounds such as vanillic acid, chlorogenic acid, caffeic acid, ferulic acid, and coumaric acid [25] and allelopathic activity in some genotypes and species of grasses, which can have an inhibitory effect on weed germination and growth [11,26,27].…”
Section: Introductionmentioning
confidence: 99%